Analisis Parallel Misalignment Pada Motor Tiga Fasa Menggunakan Digital Diagnostics System - Triyanto, Aripin; Supriadi, Oky; Maulana, Rizal (Universitas Pamulang, Prodi teknik Elektro, 2024)
Predictive industrial machine maintenance techniques have been applied in the industrial world, one of which is induction motors. The problem that occurs with induction motors is misalignment, namely damage caused by misalignment between the motor clutch and the blower load clutch. Analysis and data collection is carried out while the motorbike is operating. The resulting vibration and spectrum signals aim to facilitate data analysis according to the type of damage and vibration characteristics. Use of ADASH vibration equipment with digital diagnostics system (DDS) software and repair of misalignment using shaft alignment equipment using the laser method. The resulting data is an initial horizontal offset data value of 0.20 mm and a vertical offset of 0.17 mm. Misalignment correction produces a vertical value with an angular side of 0.00 mm, and an offset of -0.02. Meanwhile, the horizontal section has an angular side value of -0.02 mm, and an offset side of 0.01 which results in the excellent category with an operating speed of 3000 RPM. Vibration data with loads after repairs were carried out, the vibration measurement results showed that horizontal side DE was 0.55 mm/s, vertical DE 0.23 mm/s, axial DE 0.54 mm/s, horizontal NDE 0.43 mm/s, vertical NDE 0.25 mm/s, and Axial NDE 0.57 mm/s. Repairs are carried out based on vibration values in tests with loads in zone A (new machine condition) based on ISO 10816-3 standards.